Algorithm of DRM with Kinetic Damping for Finite Element Static Solution of Strain-Softening Structures - Wei Wang; Xiaozu Su (Advances in Materials Science and Engineering)
In order to deal with the divergence and instability due to the ill-posedness of the nonlinear finite element (FE) model of strain-softening structure in implicit static analysis, the dynamic relaxation method (DRM) was used with kinetic damping to solve the static increments in the incremental solution procedure so that the problem becomes well-posed. Moreover, in DRM there is no need to assemble and inverse the stiffness matrix as in implicit static analysis such that the associated computational cost is avoided. The ascending branch of static equilibrium path was solved by load increments, while the peak point and the descending branch were solved by displacement increments. Two numerical examples illustrated the effectiveness of such application of DRM in the FE analysis of static equilibrium path of strain-softening structures.